A new concept for using solar photovoltaic energy in urban water supply systems - Äurin, Bojan; Margeta, Jure (Tecnología y ciencias del agua, 2017)
Äurin, B., & Margeta, J. (November-December, 2017). A new concept for using solar photovoltaic energy in urban water supply systems. Water Technology and Sciences (in Spanish), 8(6), 47-61,DOI: 10.24850/j-tyca-2017-06-04.Â Solar photovoltaic (PV) systems can be applied very well to many areas of the water sector, such as urban water supply systems. This article presents an innovative methodology for using PV energy as a practical and sustainable solution for urban water supply systems. It presents a case study of the principal technological characteristics of an integrated energy-water system. The proposed solution consists of three parts: a PV generator and inverter, a service reservoir, and a pumping station. Given current trends, the proposed solution is slightly more expensive than conventional technologies. Nevertheless, the results obtained confirm the main idea of this research, which is that photovoltaic energy is a promising technology and provides a good solution for obtaining energy, in addition to being hydraulically sustainable urban water supply systems.